2012
DOI: 10.1002/clc.21974
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and Dependence in Activities of Daily Living in Older Adults With Severe Aortic Stenosis

Abstract: Background In the transcatheter aortic valve replacement era, characterization of functional status in older adults with aortic stenosis (AS) is essential. Gait speed (GS) is emerging as a marker of frailty and predictor of outcomes in older adults undergoing cardiovascular intervention. The objective of this study was to delineate the prevalence of slow GS, evaluate the association of GS with factors used in standard cardiovascular assessments, and evaluate the association of GS with dependence in activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…2628 Furthermore, frailty is highly prevalent and emerging as an important predictor of outcomes in the TAVI population. 29,30 In this population, the prognostic value of 6MWTD may be derived from the association of baseline 6MWTD with impaired cardiopulmonary reserve or as a marker of multisystem impairment and frailty or both. Future studies are needed to attempt to distinguish between these 2 overlapping syndromes in older adults with AS.…”
Section: Discussionmentioning
confidence: 99%
“…2628 Furthermore, frailty is highly prevalent and emerging as an important predictor of outcomes in the TAVI population. 29,30 In this population, the prognostic value of 6MWTD may be derived from the association of baseline 6MWTD with impaired cardiopulmonary reserve or as a marker of multisystem impairment and frailty or both. Future studies are needed to attempt to distinguish between these 2 overlapping syndromes in older adults with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Green et al (70,71) presented the experience at Columbia University and surprisingly showed that frailty was predictive of 1-year mortality (17% if frail vs. 7% if not frail; HR: 3.5) but not the composite of 30-day mortality or morbidity. The lack of 30-day event prediction was attributed to “adequacy of the standard selection process,” although it should be noted that there was no systematic frailty assessment on patients who had been screened out to substantiate the adequacy of the selection process and the absolute number of events was low.…”
Section: Frailty In Cvd: Current Body Of Evidencementioning
confidence: 99%
“…A serum albumin value of less than 3.5 mg/dL was considered low. Gait speed was measured by having qualified patients walk 5 meters (16.4 feet) in a designated, well-lit, open hallway at a "comfortable pace" as per the STS database guidelines [10]. If needed, patients were allowed to use a cane, walker, and oxygen support.…”
Section: Frailty Measurementsmentioning
confidence: 99%